(Invited) Surface Passivation of High-k Dielectric Materials on Diamond Thin Films. (8th September 2015) - Kovi, Kiran Kumar; Majdi, Saman; Gabrysch, Markus; Suntornwipat, Nattakarn; Isberg, Jan
Abstract : Single-crystalline CVD diamond films have excellent electrical and material properties with potential in high power, high voltage and high frequency applications that are out of reach for conventional semiconductor materials. For realization of efficient devices (e.g. MOSFET), finding a suitable dielectric is essential to improve the reliability and electrical performance of devices. In the current study, we present results from surface passivation studies by high- k dielectric materials such as aluminum oxide and hafnium oxide deposited by ALD on intrinsic and boron doped diamond substrates. The hole transport properties in the intrinsic diamond films were evaluated and compared to unpassivated films using the lateral time-of-flight technique. The MOS capacitor structure, which forms the basic building block of the MOSFET, is discussed.